Implementation of the Nine Golden Habits in Shaping Students' Religious Character - Putri Utami, Wanda; Supala; Chadidjah, Sitti; Ibrohim, Iim; Hernawati (Yayasan Mentari Madani, 2023)
Currently, character education is absolutely necessary not only for students with an early age to adolescence, but adults also need a character education. One very effective way to be applied in the formation and development of children's character and personality is habituation, one of which is through habituation. The value of religious character becomes the spirit of the purpose of character education, where in an effort to construct the words, thoughts, and attitudes of students must be based on the teachings of the religion adhered to. The purpose of this study is to identify; 1) Implementation of The Nine Golden Habits at SMA Muhammadiyah 1 Kota Bandung; 2) Supporting and inhibiting factors in the implementation of The Nine Golden Habits at SMA Muhammadiyah 1 Kota Bandung; 3) The results of the implementation of The Nine Golden Habits, on the religious character of students at SMA Muhammadiyah 1 Kota Bandung. This study used a descriptive qualitative approach. The data collection of this study used interview, observation, and documentation techniques. Data analysis methods using Miles and Huberman theory consist of data reduction, data presentation, and conclusions. The results of the implementation of The Nine Golden Habits are very beneficial for students. Where in addition to the quality of student worship becomes better, students also become more grateful, aware of the warnings given by God, more disciplined, always try to tell the truth, and humble